“E lá vem Ele”: uma etnografia da procissão do Senhor Bom Jesus dos navegantes em Penedo/AL - Torquato Júnior, Emiliano (2018)
Processions are very common cultural manifestations of popular religiosity in inner cities. In the Catholicism, they normally happen in devotion to a saint (or saints) or to the Holy Trinity, where is carried the images of Jesus Christ, of the Virgin Mary or of saints by the streets of the locality in celebration. In this way, this work aims to cast an anthropological glance on the interaction between the devotees and the saint in the Procession of the Lord Bom Jesus dos Navegantes in Penedo/AL. This is the biggest religious event inside the State bringing together devotees from the most varied regions of the country, who meet in the second week of January to honor the Bom Jesus, being the summit of the Navegantes Festivity in the city. Throughout its 133 years, the festivity has been a mark in the history of the penedian population, which is organized every year to welcome visitors, who participate in the Procession on its terrestrial and fluvial routes, in the waters of the São Francisco River. From the methodological point of view, I took part in the 2016 and 2017 celebrations, when interviews with the frequenters were carried out, with 50 of them responding to a questionnaire, which served as the basis for the first questions of the research. Through the photographic record, videos and audios, and notes in the field diary, it was possible to reflect on the relationship of the devotees with the saint. For the theoretical discussion we used the works of authors, such as: Menezes (2004); Mauss (2003a; 2003b); Turner (1974, 2005); Hannerz (1997); Van Gennep (1977); Durkheim (1996), among others.